2005
DOI: 10.1007/s00167-004-0595-4
|View full text |Cite
|
Sign up to set email alerts
|

An unusual cause for anterior knee pain: strangulated intra-articular lipoma

Abstract: Lipoma is the most frequently encountered benign soft tissue tumor. However, intra-articular lipomas are rarely seen. Anterior knee pain is a frequent complaint of adults and is of diverse etiology. This 42-year-old female patient had severe anterior knee pain, unresponsive to medical treatment. Magnetic resonance imaging revealed an intra-articular tumor of the knee joint. Arthroscopic intervention and subsequent histological examination resulted in the diagnosis of strangulated lipoma originating from infrap… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
14
0

Year Published

2006
2006
2019
2019

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 10 publications
(14 citation statements)
references
References 13 publications
0
14
0
Order By: Relevance
“…[12][13][14][15][16][17][18][19] A localized mass of fat in some patients undoubtedly represents a true neoplasm, whereas in others it may be simply a prolapse of normal fat through a deficiency in the enveloping fascia. Trauma is one of the most implicated etiological factors in lipoma formation, although its pathogenesis is not known.…”
Section: Discussionmentioning
confidence: 99%
“…[12][13][14][15][16][17][18][19] A localized mass of fat in some patients undoubtedly represents a true neoplasm, whereas in others it may be simply a prolapse of normal fat through a deficiency in the enveloping fascia. Trauma is one of the most implicated etiological factors in lipoma formation, although its pathogenesis is not known.…”
Section: Discussionmentioning
confidence: 99%
“…In the past it was believed that it only provided a blood supply to the patellar tendon. While it has been proposed that the volume and configuration of the fat pad is important to knee function 16 , other studies have suggested that the fat pad may be a source of anterior knee pain 17,18 . Importantly, recent studies provide evidence of the local production of adipokines by cells of the infrapatellar fat pad 1921 .…”
Section: Introductionmentioning
confidence: 99%
“…Infrapatellar fat pad impingement presented primarily as anterior knee pain with a variable duration of symptoms (►Tables 1 and 2). The duration was in weeks in 5 of 14 patients in case reports, [13][14][15][16] from weeks to months in 2 of 14 patients 16,17 and years in 7 of 14 patients. 16,[18][19][20][21][22] Six of the 14 patients had worsening of the pain with activity.…”
Section: Clinical Presentationmentioning
confidence: 98%
“…16,[18][19][20][21][22] Six of the 14 patients had worsening of the pain with activity. [13][14][15][16]21,22 A total of six patients described a history of trauma that predated this condition: hyperflexion in two patients 15,19 as well as chronic repetition in four patients. 14,16,18 In retrospective studies, patients presented with both acute and chronic pain with a history of injury or doing regular sporting activities.…”
Section: Clinical Presentationmentioning
confidence: 99%
See 1 more Smart Citation